How Should Ethics Consultants Weigh the Law (and other Authoritative Directives)?. Issue 4 (December 2020) - Koch, Peter
In the continuing debate about the role of the Clinical Ethics Consultant in performing clinical ethics consultations, it is often assumed that consultants should operate within ethical and legal standards. Recent scholarship has focused primarily on clarifying the consultant's role with respect to the ethical standards that serve as parameters of consulting. In the following, however, I wish to address the question of how the ethics consultant should weigh legal standards and, more broadly, how consultants might weigh authoritative directives, whether legal, institutional, or professional, against other normative considerations. I argue that consultants should reject the view that authoritative directives carry exclusionary reason for actions and, further, ethicists should interpret directives as lacking any moral weight qua authoritative directive. I then identify both implications and limitations of this view with respect to the evolving role of the ethics consultant in an institutional setting, and in doing so propose the kinds of considerations the ethicist should weigh when presented with an authoritative directive.